Conflicting outcomes of alternative energies: agricultural methane emissions and hydroelectricity, 1975–2015. (8th September 2022) - Sikirica, Amanda; Theis, Nicholas; Betancourt, Mauricio
Abstract: Mitigating emissions from methane, a potent greenhouse gas (GHG), is a critical task of fossil fuel alternatives in energy generation as well as in other sectors with large environmental impacts such as agriculture. Agricultural methane emissions have not been given sufficient attention in social science approaches to the human dynamics of GHG emissions. Given the importance of methane emissions, the need for renewable energy development, and the relationship between hydropower and agricultural systems, we ask: does hydroelectricity development influence agricultural methane emissions? If so, under what socioeconomic conditions? Using the World Bank's World Development Indicators and FAO data, we present fixed-effects models with robust standard errors to predict agricultural methane emissions from 1975–2015. Our results show that in low middle income nations and across all nations, increased hydroelectricity generation was associated with increased agricultural methane emissions during this period. We suggest hydroelectricity generation and affluence are associated with a suite of agricultural techniques, including the organization of agricultural waterbodies and animal feed, which may contribute to higher levels of agricultural methane emissions. Given the pressing need for alternatives to fossil fuels, we recommend further examination of the economic conditions for implementing alternative fuels to avoid unintended environmental harms, including those which directly counteract the intended emissions-reduction purpose of these alternatives.